The Effectiveness of Hypnobreastfeeding and Marmet Techniques in Improving Breast Milk Production - Rusmilawaty, Rusmilawaty; Hapisah, Hapisah; Rafidah, Rafidah (Journal of Maternal and Child Health, 2021)
Background: Breast milk as a natural food is the best food that a mother can give to a newborn child. Judging from the factor of peace of mind and mind to produce good breast milk, the mental condition and mind must be calm. The psychological state of the mother who is depressed, sad, stressed, anxious, depressed and tense will reduce the volume of breast milk. One of the methods that can be done to increase milk production is Hypnobreastfeeding and marmet technique.The purpose of this study was to examine the effectiveness of hypnobreastfeeding and marmet techniques in increasing breast milk production. Subjects and Method: This study used a quasi-experimental design with a non-equivalent control group design. The population in this study were pregnant women ≥36 weeks in the Banjar District Health Center in 2019 (Aranio, Astambul and Mataraman). The sample of the study was 45 pregnant women ≥36 weeks consisting of 3 groups, namely the group that received hypnobreastfeeding treatment, the group that received the marmet technique treatment and the group that did not get the treatment consisted of 15 people each. Bivariable analysis used the one way anova statistical test. Results: Breast milk production in the hypnobreasfeeding group Hypnobreastfeeding vs control group (mean= 2.00; SD= 0.50; p= 0.001); The marmet technique vc marmet technique group (mean= 1.87; SD= 0.50; p= 0.002). The marmet technique vc control group (mean= -18.7; SD= 0.50; p= 0.002). Conclusion: Pregnant women should get hypnobreasfeeding during pregnancy and after giving birth, health workers, especially midwives, to have hypnobreasfeeding skills.